The impact of specific anaerobic exercises on the development of kinetic performance speed and skill level for the backcourt smash in volleyball - Ali Khalid Mukhlif; Khalil Ibrahim Sulaiman; Qusay Rashid Sabti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study examined the impact of specific anaerobic exercises on the development of kinetic performance speed ("movement speed") and the skill level of volleyball players in executing the backcourt smash (from position 6). The researchers employed an experimental methodology using a single experimental group with pre- and post-tests. The sample included 12 players from the Abu Risha Volleyball Club participating in the premier league. Over eight weeks, the players underwent three training sessions per week, with three training sessions per week. The practical part of the training sessions began with the main section, each lasting 15 minutes dedicated to anaerobic exercises. The post-test results were statistically analyzed and discussed scientifically, supported by relevant academic sources. The researchers concluded that the specific anaerobic exercises significantly enhanced both the straight and diagonal kinetic performance speeds and skill levels of the backcourt smash from position 6, particularly towards positions 1 and 5. The researchers recommend adopting these exercises when aiming to develop the kinetic performance speed or skill level of volleyball players, to achieve high-level performance in the game.